2021
DOI: 10.1007/s13369-021-06165-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Participants Using Counting-Based Secret Sharing via Involving Matrices and Practical Steganography

Abstract: Secret sharing is an approach for accessing sensitive information by several authorized participants. It shares the secret key in different forms among several authorized participants, where a certain number of which is required to retrieve the original secret. This secret sharing raised a new practicality challenge of human secrecy memorization as well as limited number of users allowed, which have been addressed within this work. This paper examines two particular secret sharing techniques known as the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It has been recently found that malicious users can disrupt the seamless functioning of CQAs. Identifying such users and developing ways to stop them also need immediate attention, not as reported for increasing number of participants adopting counting‐based secret sharing [191]. Besides topic modelling, the tag suggestion for a new question has attracted very limited research [192].…”
Section: Open Research Issues Directions and Challengesmentioning
confidence: 99%
“…It has been recently found that malicious users can disrupt the seamless functioning of CQAs. Identifying such users and developing ways to stop them also need immediate attention, not as reported for increasing number of participants adopting counting‐based secret sharing [191]. Besides topic modelling, the tag suggestion for a new question has attracted very limited research [192].…”
Section: Open Research Issues Directions and Challengesmentioning
confidence: 99%
“…This is a benefit of using counting-based secret sharing, as principally discussed for image steganography optimization within [38]. The challenge in the extraction algorithm is that extraction can be from any part of the watermarked text [39], not always from the beginning [40], and it is not known where shares start and end in the watermarked text part [41]. A solution is to test all possibilities of the positions of shares.…”
Section: Extracting Algorithmmentioning
confidence: 99%
“…The main difference between them is the alphabet where DNA and RNA sequences are represented by four letters while protein sequences are represented by 20 letters [55]. This memory sharing strategy can benefit boost-up parallel sharing via counting-based secret-sharing [56] and its enhancement in matrices [57] as well as increasing shares [58], trustfulness hiding [59], and sharing regularity optimization [60]. The proposed method can be extended and generalized to cover genomic sequences since, computer-wise, all of them are represented as a string of letters.…”
Section: Possible Extension To Genomic Sequencesmentioning
confidence: 99%